Religion, Institutionalization and Legitimation of the Creed: Beyond Institutional Fundamentalism - Danner, Leno Francisco; Bavaresco, Agemir; Danner, Fernando (Numen, 2021)
This article argues that the association between institutionalization and strong epistemological, political, anthropological and ontological objectivity leads to institutional fundamentalism in three basic and problematic aspects for societal-cultural-institutional current dynamics: first, the institution’s centralization and monopolization of the constitution, legitimation and public foment of the creed, so that the institution becomes self-referential, self-subsisting and autonomous regarding common sense and common people, as opposed to other religious institutions; second, the institution’s vertical and direct affirmation and imposition on believers and non-believers of essentialist and naturalized foundations which do not seriously consider the differences as epistemological-political subjects, practices and codes; third, the institution’s self-affirmation of its special core-role in terms of linking Earth and Heaven, people and God, so that it becomes the one and supreme institution representing God on Earth, delegitimizing other religious institutions and popular practices as alternative ways to God, alternative ways of life and epistemological, political, anthropological and ontological grounding. From that point, the article advocates that only the weakening of the essentialist and naturalized foundations, the moderation or even the abandonment of their problematic parts, as the deconstruction of institutional self-referentiality, self-subsistence and autonomy regarding common sense and common people, as well as of the opposition between religious institutions one to each other, can tackle the problem of fundamentalism, enabling the valuing of differences as epistemological-political subjects and the performance of an ecumenical and pluralistic dialog-praxis which assembles all peoples into a same minimal project of global peace, justice and solidarity.